Holocene record of large explosive eruptions from Chaitén and Michinmahuida Volcanoes, Chile - Amigo,Álvaro (Servicio Nacional de Geología y Minería (SERNAGEOMIN), 2013)
Tephra fall deposits and one large ignimbrite close to Chaitén and Michinmahuida Volcanoes were analyzed for chemistry and radiocarbon dated to correlate the eruptive units and establish the timing of eruptions. These data suggest that both volcanoes were the source of large (VEI ≥5) and small to moderate (VEI <5) explosive eruptions throughout the Holocene. Four deposits are associated with volcanic activity from Chaitén Volcano, with two from Plinian eruptions at 9.9-9.5 and 5.3-4.9 (cal) ka BP that also generated pyroclastic density currents. The last event recognized from Chaitén (prior 2008) occurred a few hundred years ago, producing deposits that are similar to those of the 2008 eruption. All products from Chaitén are high-silica rhyolites; whole-rock compositions are indistinguishable but glass compositions are subtly different for some of the units. Seven deposits are related to eruptions of Michinmahuida Volcano, including a Plinian fall deposit at 7.6-7.3 ka BP and a large ignimbrite deposit at 10.5-10.2 ka BP. The chemical compositions of these products range from andesite to dacite. The last substantial explosive eruption event from Michinmahuida Volcano appears to have been a 0.5-0.3 ka BP sub-Plinian eruption, although younger scoria fall deposits likely derived from local pyroclastic cones are also found. Both volcanoes pose a wide variety of potential hazards to the region ranging from those derived from ignimbrite-forming eruptions to pyroclastic-cone formation. Valleys adjacent to the volcanoes were the areas most heavily affected by volcanic activity, because they were inundated by pyroclastic density currents and lahars. However, even regions located tens of kilometers east and north of the volcanoes experienced accumulations of tephra, which could harm both agriculture and infrastructure if similar events occurred today.